Development of NumberTunes media assisted by song to improve critical thinking skills about fraction comparison in elementary school - Rahajeng Achyani; Putri Yanuarita Sutikno (Universitas Muhammadiyah Malang, 2025)
Students' difficulty understanding the basic concept of abstract fraction comparison is the background of this research. Using learning media such as interactive multimedia in helping learning activities in the class can solve these problems. This research aims to develop a media known as Song-assisted NumberTunes that is feasible, interesting, and effective in improving students' critical thinking skills on fraction comparison material. Song-assisted NumberTunes media is a learning media that combines songs, learning videos, and games. This R&D uses the ADDIE model (analyze, design, develop, implement, and evaluate). The results showed that the use of technology in developing learning media as an innovation has an impact on the progress of student outcomes, creating a different learning atmosphere, which makes the learning process itself meaningful, so that the goals can be achieved, based on the research, shown that Song-assisted NumberTunes media has been tested as effective and usable for learning fraction comparison in the fifth grade.